The pyrolysis of oak with polyethylene, polypropylene and polystyrene using fixed bed and stirred reactors and TGA instrument. (1st October 2021) - Abbas-Abadi, Mehrdad Seifali; Van Geem, Kevin M.; Fathi, Maryam; Bazgir, Hossein; Ghadiri, Mohammad
Abstract: The pyrolysis of Iranian oak wood and waste plastics has been studied under different oak/plastic ratios and using different zeolite based catalysts. Pyrolysis of oak/plastics using a fixed bed reactor, resulted in the production of a liquid with a high oxygen content. The resulting organic liquids were re-pyrolyzed and deoxygenated using the zeolite catalysts in a batch stirred reactor under initial pressure of hydrogen and nitrogen (20 bars). The pressurized pyrolysis using HZSM-5 with a medium pore size of the 0.55 nm pore size gave the best de-oxygenation performance in comparison with the other catalysts. In TGA study, the slope of TGA curve and the onset temperature of degradation helped to assess degradation mechanisms and the related thermal stability. During thermal copyrolysis, the polymer melt penetrated and covered the oak particles and acted as an insulator. In addition to insulation, polypropylene and polystyrene partially and simultaneously degraded with cellulose, which led to increased cross interactions compared to polyethylene. Degradation of deposited melt polymer on the oak particles led to the formation of a thin layer coke covering the oak particles. The coke layer further increased the thermal stability of the remaining cross-linked lignin and resulted in a slower degradation. Graphical abstract: Image 1 Highlights: Polymer melt act as insulator for oak particles and increase thermal stability. Polymers boost the crosslink mechanism in oak degradation. In copyrolysis, the crosslinked lignin tends to degrade with lower rate. The simultaneous overlap of oak degradation with polymers affects the degradation trend. The re-pyrolysis under HZM-5 and hydrogen, decrease the oxygenated obviously. The de-oxygenation can affect the pyrolysis products obviously.